2004
DOI: 10.1111/j.1524-4725.2004.30431.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular 1320-nm Laser Closure of the Great Saphenous Vein: A 6- to 12-Month Follow-up Study

Abstract: At 6 months or greater follow-up, a 5-W, 1320-nm intravascular laser with 1 mm/s automatic pullback, delivered through a diffusion-tip fiber, is safe and effective in treating an incompetent great saphenous vein up to 1.2 cm in diameter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
94
0
4

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 36 publications
2
94
0
4
Order By: Relevance
“…Indeed, the obliteration rate was found to be 100% over the entire follow-up period (2.5 years) (Table III), which was clearly better than observed in the previous studies performed without ligation. [11][12][13][14][15][16][17][18] Consistent with this finding, skin lesions and subjective symptoms were remarkably improved after treatment (Figure 1). Furthermore, no major complications, including DVT, were noted.…”
Section: Discussionsupporting
confidence: 73%
“…Indeed, the obliteration rate was found to be 100% over the entire follow-up period (2.5 years) (Table III), which was clearly better than observed in the previous studies performed without ligation. [11][12][13][14][15][16][17][18] Consistent with this finding, skin lesions and subjective symptoms were remarkably improved after treatment (Figure 1). Furthermore, no major complications, including DVT, were noted.…”
Section: Discussionsupporting
confidence: 73%
“…Many different wavelengths and different types of optical fibers have been tested in attempts to achieve this objective. [1][2][3][4][5][6][7][8] Several authors have demonstrated that all of the wavelengths employed to treat varicose veins are equally capable of producing the desired anatomic results. The fundamental differences between different wavelengths are related to occurrence of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…1 Since then, there has been increasing progress in laser technology, and numerous studies have been performed using different wavelengths and types of laser. [2][3][4][5][6][7] The Food and Drug Administration (FDA)-approved lasers today are 810, 940, 980 and 1470 nm diode lasers and 1319 and 1320 nm neodymium-doped yttrium aluminium garnet (Nd:YAG) lasers. In parallel to advances in laser technology, studies began being performed concerning thermal ablation of the saphenous vein using radiofrequency energy, and permission for the use of radiofrequency energy in endovenous ablation was granted by the FDA in 1999.…”
Section: Introductionmentioning
confidence: 99%